ANALISIS POLA KOMUNIKASI NONVERBAL OLEH GURU DALAM PEMBELAJARAN DI SMALB BINA ANAK BANGSA PONTIANAK - Sagita, Labora Nora; Sulistyarini, Sulistyarini; Imran, Imran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe present study was undertaken to analyze the patterns of nonverbal communication by the teachers in teaching and learning process at SMALB Bina Anak Bangsa Pontianak. The general problem of this study was â€œHow are the Patterns of Nonverbal Communication by the Teachers in teaching and learning process at SMALB Bina Anak Bangsa Pontianakâ€.Â  The researcher used descriptive analysis to present the findings of the research. The techniques of data collection for collecting the data were observations, interviews and documents with the tools such as interview guide, observation schedule, data sheet and camera. The results of this study were (1) Kinesics ran well which was proved by the hand movements, posture and teachersâ€™ specific facial expressions; (2) Haptics ran well which was proved by the touches teachers did toward the students; and (3) Vocalics ran well which was proved by the teachersâ€™ diction and intonation while teaching the students.Â Keywords : Nonverbal Communication, Teacher, Learning, Special School